Kajian Semangat Patriotisme dan 1malaysia dalam Kalangan Mahasiswa di Timur Tengah - Ghazali , Mohd Rumaizuddin; Jalani, Mohd Rushdan (‘Abqari Journal, 2015)
This article focuses on the understanding of the ideas of patriotism and 1Malaysia amongst the Malaysian students overseas. It also highlights the hopes and expectations of these Malaysian students in the Middle East on the national leadership. In general, through a series of interview session, the Malaysian students in the Middle East are still grappling with the 1Malaysia ideas including their patriotism spirit. This requires deeper and more frequent clarification through grassroot approach directly focused on these Malaysian students in the Middle East.